Main Economic Problems: Conventional and Islamic Perspectives - Yosi Mardoni; Muhammad Fauzi; Duhriah Duhriah; Faisal Efendi; Kusnadi Kusnadi (Journal of Islamic Economics and Finance Studies, 2025)
This study aims to analyze the main economic problems from conventional and Islamic perspectives. This is based on the fact that conventional economists view the main problem of economics as scarcity. Scarcity occurs as a result of an imbalance between society's needs. However, Muslim economists have different views from conventional economists, even within Muslim economists they still have different opinions regarding the main economic issues. In this research, the methodology used is descriptive with a qualitative approach. The data used is secondary data in the form of literature which discusses the object of this research. Research analysis was carried out in steps, such as material collection, descriptive analysis, discussion and intuitive-subjective evaluation of the material. The findings show that there is a fundamental difference in the perspective on the main economic problems between conventional economic views and Islamic economics.. Conventional economics focuses more on product objects so that the focus of problems is centered on the limitations and scarcity of products in order to meet human physical needs only. This perspective is different from Islamic economics which places greater emphasis on human objects so that the focus of problems is not only focused on products alone, but also on human empowerment to be able to prosper themselves, their families, society and the country. This is one of human efforts in realizing/maintaining Maqashid Sharia (Mashlahah) and achieving Falah. Islam views that human dignity is an essential thing, so that every human being plays a role in achieving happiness in life.